The complete human body the definitive visual guide - Roberts, Alice M. (Dorling Kindersley, 2016)
A guide to the development, form, function, and disorders of the human body. It uses 3D computer-generated artworks to bring the body to life in a whole new way, covering everything from bones, muscles, and joints to mental health disorders. It also helps you learn about over 200 diseases and how they afflict the human body.